1996
DOI: 10.1042/bj3200473
|View full text |Cite
|
Sign up to set email alerts
|

Spreading of methylation along DNA

Abstract: Mouse DNA methyltransferase is able to catalyse the transfer of a methyl group to certain CG-containing single-stranded oligonucleotides. The presence of a methylcytosine is required for efficient transfer. This methylcytosine may or may not be on the same oligonucleotide as that containing the accepting CG dinucleotide. When the accepting CG dinucleotide forms part of an unmethylated CG dinucleotide pair, its accepting activity is dramatically reduced. This provides the potential for methylation to spread alo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
18
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 19 publications
3
18
0
Order By: Relevance
“…We confirmed that expression status of selected bar and non-selected cecropin B was independent within the same genomic locations. This means the inactivation of cecropin B does not spread over to the adjacent bar gene, which is consistent with the conclusion of some previous reports (Vain et al, 2002;Kohli et al, 2003) but argues against others (Lindsay et al, 1996).…”
Section: Stability Of Transgene Expression In Crossing Transmissionsupporting
confidence: 81%
“…We confirmed that expression status of selected bar and non-selected cecropin B was independent within the same genomic locations. This means the inactivation of cecropin B does not spread over to the adjacent bar gene, which is consistent with the conclusion of some previous reports (Vain et al, 2002;Kohli et al, 2003) but argues against others (Lindsay et al, 1996).…”
Section: Stability Of Transgene Expression In Crossing Transmissionsupporting
confidence: 81%
“…34,35 The spreading of methylation from the foci of methylated CpG sites has been demonstrated in vitro in cultured cells and in transgenic mice. 24,32,[36][37][38] Methylation spreading has also been observed to occur as a function of aging and neoplasia. 39,40 In the colon, methylation of the MYOD1 CpG island increases progressively with age.…”
Section: Discussionmentioning
confidence: 99%
“…The significance of this degree of methylation is uncertain; however, regional DNA methylation can be influenced by Alu (44) or cis-acting sequences (45). Once de novo methylation has been "seeded," spreading of methylation may be possible (46).…”
Section: Discussionmentioning
confidence: 99%